2021
DOI: 10.1177/23743735211039925
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Nursing Students in the Care for Patients Diagnosed With COVID-19: A Qualitative Study

Abstract: The present study examined the experiences of nursing students in the care of patients diagnosed with coronavirus disease 2019 (COVID-19). This qualitative study was performed based on inductive qualitative content analysis in 2020. The samples were 10 nursing students who were selected purposively from the emergency and intensive care unit wards of hospitals affiliated with Mazandaran University of Medical Sciences in Iran. Data were collected through semistructured and individual interviews and analyzed simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…This connects with findings reported by Nabavian and colleagues (2021). Their participants also said they even hid from their families and friends while serving in Covid-19 wards so as not to generate anxiety ( Nabavian et al, 2021 ). These aspects are also described in other qualitative studies ( Canet-Vélez et al, 2021 , Roca et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This connects with findings reported by Nabavian and colleagues (2021). Their participants also said they even hid from their families and friends while serving in Covid-19 wards so as not to generate anxiety ( Nabavian et al, 2021 ). These aspects are also described in other qualitative studies ( Canet-Vélez et al, 2021 , Roca et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As to nursing students, insights into their experience during the first wave of the pandemic while attending academic courses (Masha’al Dina et al, 2020 ) or clinical placement ( Eweida et al, 2020 ) are emerging. However, studies considering the clinical practice experience while caring for Covid-19 patients ( Casafont et al, 2021 , Galvin et al, 2020 , Nabavian et al, 2021 , Rodríguez-Almagro et al, 2021 ) are scarce. To the best of our knowledge, no study has examined this experience in Italy, where the pandemic strongly hit since February 2020 and clinical placements were almost wholly suspended.…”
Section: Introductionmentioning
confidence: 99%
“…As of the 12 studies, 6 were conducted in Spain (Canet-Vélez et al, 2021;Casafont et al, 2021;Gómez-Ibáñez et al, 2020;Ramos-Morcillo et al, 2020;Roca et al, 2021;Velarde-García et al, 2021), 2 in USA, 1 in England (Godbold et al, 2021), 1 in Jordan (Suliman et al, 2021), 1 in Iran (Nabavian et al, 2021), and 1 in Croatia (Lovrić et al, 2020). Included studies used semi-structured online interviews using Zoom, Skype, and Microsoft teams (n=7), focus group (n=1), face to face interview (n=2), archived letters ( n=1), and open-ended questionnaire sent via email (n=1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Previous studies have identified that nursing students caring for patients with COVID-19 have expressed feelings of psychological stress, fear of patients, and mental conflict as they worried about becoming ill themselves or transmitting the virus to others. [6] Lancaster et al ( 2021) [1] also reported that graduating nurses experienced stress related to the conflict between their obligation to keep themselves and their loved ones safe while caring for those with COVID-19. For some students, the fear of infection in the classroom was not as significant as it was in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%